Evaluating the Impact of Pontic Geometry on Load to Failure and Displacement in Implant-Supported Monolithic Zirconia Prostheses: An In Vitro Analysis - Silvia de la Cruz-Jiménez; Paloma Martínez-Alcaraz; Javier Flores-Fraile; Rubén Agustín-Panadero; Ana Belén Lobo-Galindo; Concepción Carbonell-López; Álvaro Zubizarreta-Macho (Journal of Functional Biomaterials)
The pontic design may influence the load-to-failure performance of fixed implant-supported screw-retained monolithic zirconia prostheses. This study aimed to evaluate the effect of pontic geometry on the fracture resistance of such restorations. Forty restorations were designed using dental CAD software and divided into four groups (n = 10 each): (A) Flat + Wide—pontics with a flat contour, 10 mm in width and 8 mm in height; (B) Concave + Wide—pontics with a concave contour, 10 mm in width and 5.5 mm in height; (C) Flat + Narrow—pontics with a flat contour, 6 mm in width and 8 mm in height; and (D) Concave + Narrow—pontics with a concave contour, 6 mm in width and 5.5 mm in height. All specimens underwent thermal and mechanical cycling, followed by a fracture load test using a three-point bending setup. Maximum fracture loads and displacements were analyzed using one-way ANOVA. Statistically significant differences were observed among the groups for both load to failure (p = 0.001) and displacement (p = 0.002). These findings indicate that pontic geometry significantly influences the fracture resistance and deformation behavior of monolithic zirconia prostheses.